Effects of gamma irradiation on non-polar GaN films deposited on sapphire using pulsed laser deposition - Rajgoli, Tahir; Sant, Tushar; Jejurikar, Suhas M.; Hinge, Sandip; Banpurkar, Arun; Dahiwale, S. S.; Late, Datta (Applied Surface Science, 2024)
The GaN films/layers exposed to gamma-radiations is known to harvest defects and vacancies in the crystals producing donor, acceptor and recombination centers within the bandgap. Therefore it is important to investigate and study the gamma- ray irradiation effects on various physical and chemical properties of a material before any optoelectronic and/or electronic devices are being fabricated. To avoid Stark effect which is observed in most of the optoelectronic devices fabricated using GaN films grew along polar face, use of non-polar GaN films is suggested by researchers. To address such issues the article reports the investigations of physical and chemical properties of non-polar GaN films grown on polar substrate using pulsed laser deposition, which were exposed to the 60Co gamma rays varying dose values. Resistive nature against the impairment of the films caused by gamma-rays observed herewith is highly encouraging, suggesting the use of non-polar GaN films as radiations harden material suitable for fabricating new generation gamma-ray detectors. To our knowledge very limited information is available that report such investigations.
Keywords: Gallium nitride; Gamma rays; PL emission; pulsed laser deposition